Research on the design of Chaoshan intelligent tableware based on digital image processing technology - Zhuopeng, Li; Muhammad Jameel, Mohamed Kamil (2022)
Smart tableware is a tool produced along with smart catering. It is a smart food container designed based on the Internet of Things, cloud computing and artificial intelligence technology through new technologies and information technology. Based on digital image processing technology, this paper develops and designs smart tableware, introduces the digital image calibration principle and sampling quantification method adopted by Chaoshan smart tableware, and then uses image segmentation and binarization analysis, color digital image processing and analysis technology to explore The abstract beauty of Chaoshan smart tableware. The development of this creative product not only brings convenience to our use, but also a symbol of our cultural innovation.